2022
DOI: 10.3389/fendo.2022.896511
|View full text |Cite
|
Sign up to set email alerts
|

Genomic DNA Methylation in Diabetic Chronic Complications in Patients With Type 2 Diabetes Mellitus

Abstract: AimTo explore the relationship between genomic DNA methylation and diabetic chronic complications.Methods299 patients with type 2 diabetes mellitus (T2DM) hospitalized in the Second Affiliated Hospital of Soochow University were enrolled. We divided the patients into different complications groups and corresponding non-complication groups. Clinical and biochemical parameters were compared between the two groups. The level of genomic DNA methylation in leukocytes was determined by high-performance liquid chroma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Second, recent studies point to common pathology/pathophysiological mechanisms. For instance, a recent report shows a low level of genomic DNA methylation in DPN of type 2 diabetic patients but not in other complications of diabetes, such as diabetic retinopathy or nephropathy, indicating that a reduced level of genomic DNA methylation is a relatively specific risk factor for DPN [68]. Similarly, when investigating DNA methylation and gene expression in human sural nerve biopsies, Guo et al found that DNA methylation is a mechanism in the regulation of gene expression in DPN [69,70].…”
Section: B 12 Deficiency-induced Neuropathy and Diabetic Neuropathy S...mentioning
confidence: 99%
“…Second, recent studies point to common pathology/pathophysiological mechanisms. For instance, a recent report shows a low level of genomic DNA methylation in DPN of type 2 diabetic patients but not in other complications of diabetes, such as diabetic retinopathy or nephropathy, indicating that a reduced level of genomic DNA methylation is a relatively specific risk factor for DPN [68]. Similarly, when investigating DNA methylation and gene expression in human sural nerve biopsies, Guo et al found that DNA methylation is a mechanism in the regulation of gene expression in DPN [69,70].…”
Section: B 12 Deficiency-induced Neuropathy and Diabetic Neuropathy S...mentioning
confidence: 99%
“…The level of DNA methylation was also altered in peripheral blood leukocytes of T2DM patients with late complications. Lower levels of genomic DNA methylation were significantly associated with the risk of diabetic polyneuropathy but were not associated with DKD or other chronic T2DM complications [ 94 ]. As shown in a recent EWAS study in an Indian population, specific methylation patterns can be used as biomarkers for stratification of T2DM patients with different clinical outcomes as they enable separating patients with good glycemic control and dyslipidemia from the other patients [ 95 ].…”
Section: Molecular Mechanisms and Molecular Genetics Of Sglt Action—p...mentioning
confidence: 99%
“…A recent metaanalysis of 27 studies of 5924 youths with T2D showed prevalence of diabetic retinopathy of 2% at <2.5 years diabetes duration, of 5% at 2.5–5 years duration, and of 29% at >5 years duration 14 . There is evidence of genomic factors contributing to risk of the development of complications in T2D youths 15 . Understanding this burgeoning epidemic and developing more effective therapeutic approaches will be crucial in the coming years.…”
Section: Country Cases Person‐years Cases/100000 Person‐yearsmentioning
confidence: 99%
“…14 There is evidence of genomic factors contributing to risk of the development of complications in T2D youths. 15 Understanding this burgeoning epidemic and developing more effective therapeutic approaches will be crucial in the coming years.…”
mentioning
confidence: 99%